두드러기의 한의치료 임상-국내 증례연구 분석 - 하재운; 황윤경; 윤영주; Jaewoon Ha; Yungyeong Hwang; Youngju Yun (대한예방한의학회지, 2023)
Objective : To investigate syndrome identification, herbal prescriptions, acupuncture point and other treatment, this study systematically reviewed case studies on Korean medicine (KM) treatment for urticaria. Method : Literature searches were performed on four Korean database; OASIS, RISS, KTKP and NDSL. Studies published before December 2022 were categorized and analyzed according to the herbal prescriptions. Results : Thirty-three studies including 16 case series and 17 single case reports were included in our review and the total number of patients was 523. Ancient prescriptions (古方) were used in 7 studies and prescriptions of Sasang constitutions were used in 8 studies and 18 studies used prescriptions of posterity (後世方). Wind-Heat (風熱) and syndrome identifications associated with digestive function were used frequently. Nineteen studies used acupuncture combined with herbal medicine and mainly used acupoints were ST36 (足三里), LI4 (合谷), LI11 (曲池), LR3 (太衝), SP6 (三陰交), CV12 (中脘), SP10 (血海). External herbal medicine was used in only 3 studies. Conclusion : To increase the cure rate of KM, various prescriptions should be used according to the symptom and stage of urticaria. Diversification of herbal formulations and the development of new external medicines are also necessary to conduct additional clinical studies with a high level of evidence.